Dysplasia at the Anal Transition Zone after IPAA - Church, James (Clinics in Colon and Rectal Surgery, 2022)
Ileal pouch-anal anastomosis is a popular way of reconstruction the gastrointestinal tract after total proctocolectomy for ulcerative colitis. The pouch-anal anastomosis is usually stapled, which requires the preservation of a small amount of upper anal canal and lower rectum. This includes the anal transition zone (ATZ), a surprisingly small and irregular ring of tissue at and just above the dentate line. The ATZ and rectal cuff is prone to inflammation and neoplasia, particularly in patients who had a colon cancer or dysplasia at the time their large bowel was removed. This high-risk group needs ATZ/rectal cuff surveillance before and after the surgery. Those without colorectal dysplasia preoperatively are at low risk of developing ATZ/rectal cuff dysplasia postoperatively and follow-up can be more relaxed. Treatment of ATZ dysplasia is difficult and may mean mucosectomy, pouch advancement, pouch removal, or a redo pelvic pouch.
Keywords: ileal pouch-anal anastomosis; anal transition zone; dysplasia